Mahārāshṭra-bhāshābhyāsa : Mahārāshṭra śabdakośa-prastāvanāsaṅgraha - Dāte, Yaśavanta Rāmakrshṇa, 1891- (SAMP early 20th-century Indian books project ;, 1938)
Compilation of prefaces written to various volumes of Mahārāshṭra śabdakośa, on Marathi philology.